Labor Partnership in early Islamic Law (Journal of the College of Education for Women, 2019)
In terms of each party's contribution to the common venture, partnership felt in several categories. It would be a complete partnership, that is, one in which all partnership, both capital and service; It could be an arrangement like the commenda (Arabic : Mudãraba , muqãraba , girãd) in which one party supplied the capital and the other service .In Malikite and Hanaifite Law, It would take the form of a labor partnership, that is, one in which the only investment on the part of all its members was their skill or labor. In this last category of partnership, the captil itself considered solely or primarily of the labor of the partners.